Analisis Konsep Tasawuf dan Implikasinya terhadap Kesehatan Mental - Lingga Kirane; Umi Nur Kholifah (Al-Kindi, 2025)
Sufism (tasawuf) emerges as a spiritual approach with significant potential to support mental health through practices such as dhikr, muraqabah, hudhur al-qalb, tafakkur, and the internalization of values such as sincerity, patience, and trust in God. This study employs a Systematic Literature Review (SLR) guided by PRISMA standards to identify, evaluate, and synthesize empirical evidence on the relationship between Sufistic practices and mental health outcomes. Literature searches were conducted across international and national databases with inclusion criteria focusing on empirical studies exploring Sufi practices and indicators of mental well-being. Findings indicate that Sufism consistently contributes to reducing anxiety, stress, and depression while enhancing emotional stability, inner peace, and psychological well-being. Sufi-based interventions demonstrate alignment with modern psychotherapeutic mechanisms and provide notable physiological and emotional benefits. Although methodological quality varies across studies, the overall evidence supports the potential of Sufism as a complementary and holistic approach within psychospiritual therapy and mental health services. Thus, Sufism can be considered a relevant and culturally grounded intervention for supporting mental health in contemporary society.